2004
DOI: 10.1037/0735-7044.118.6.1352
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone's Analgesic, Anxiolytic, and Cognitive-Enhancing Effects May Be Due in Part to Actions of Its 5α-Reduced Metabolites in the Hippocampus.

Abstract: Although testosterone (T) may decrease anxiety and enhance cognitive performance, its mechanisms are not well understood. The authors hypothesized that if T's effects are mediated in part through actions of its 5alpha-reduced, nonaromatizable metabolite dihydrotestosterone (DHT) and/or its 3alpha-hydroxysteroid dehydrogenase reduced metabolite 3alpha-androstanediol (3alpha-diol) in the hippocampus, then T, DHT, and 3alpha-diol administration should produce similar behavioral effects concomitant with elevating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 88 publications
4
109
4
Order By: Relevance
“…The lack of findings on pain sensitivity is somewhat surprising because previous studies have found that testosterone levels do relate to pain sensitivity and anxiety [42,43]. Interestingly, low levels of testosterone have been shown to enhance the fear response as measured by freezing and fear-induced analgesia [44], suggesting the possibility that the ET animals in the current study may show reduced aggression because of enhanced fear.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…The lack of findings on pain sensitivity is somewhat surprising because previous studies have found that testosterone levels do relate to pain sensitivity and anxiety [42,43]. Interestingly, low levels of testosterone have been shown to enhance the fear response as measured by freezing and fear-induced analgesia [44], suggesting the possibility that the ET animals in the current study may show reduced aggression because of enhanced fear.…”
Section: Discussioncontrasting
confidence: 47%
“…However, the observed weight reduction is due to ethanol exposure during the second half of gestation [22] and is not a result of undernutrition since there are no body weight differences across dam groups. Thus, dissociating the effect of ethanol on the development of the body from that on the brain is not possible at least in an in vivo model.The lack of findings on pain sensitivity is somewhat surprising because previous studies have found that testosterone levels do relate to pain sensitivity and anxiety [42,43]. Interestingly, low levels of testosterone have been shown to enhance the fear response as measured by freezing and fear-induced analgesia [44], suggesting the possibility that the ET animals in the current study may show reduced aggression because of enhanced fear.…”
contrasting
confidence: 47%
“…Edinger and Fry [74] further found that systemically administered testosterone, dihydrotestosterone, or 3α-androstanediol all increased analgesia in the tail flick and paw lick paradigms. When administered intrahippocampally, these three steroids were also analgesic in the tail flick paradigm but only testosterone and 3α-androstanediol were analgesic in the paw lick paradigm.…”
Section: Analgesiamentioning
confidence: 99%
“…Metabolic syndromes may have a correlation with anxiety and depression, but its nature is unclear (6). Among all behavioral parameters, anxiety is thought to be most sensitive to testosterone and this hormone is either endogenous or exogenous and has been reported to have anxiolytic effect in the elevated plus maze (EPM) test (7,8). In addition, gonadectomy (GDX) results in anxiety-like behavior in male rats and increased exhibition of signs of anxiety in open field test (OFT) and EPM test (8).…”
Section: Introductionmentioning
confidence: 99%
“…Among all behavioral parameters, anxiety is thought to be most sensitive to testosterone and this hormone is either endogenous or exogenous and has been reported to have anxiolytic effect in the elevated plus maze (EPM) test (7,8). In addition, gonadectomy (GDX) results in anxiety-like behavior in male rats and increased exhibition of signs of anxiety in open field test (OFT) and EPM test (8). The genus Pistacia belongs to the Anacardiaceae family, and the most popular species of pistacia are Pistacia lentiscus, P. atlantica Desf., P. terebinthus L., P. vera L., and P. khinjuk Stock.…”
Section: Introductionmentioning
confidence: 99%